The Effect of Organizational Support and Competency on Employee Performance in PT. Andalan Mandiri Busana Boyolali - Ekowati, Ekowati; Cahyono, Cahyono (Faculty of Economics and Business UNTAG Semarang, 2023)
This study aimed to determine the effect of organizational support and competence on employee performance. The population used is all employees who work at PT. Andalan Mandiri Busana Boyolali with a total of 1018 people, while the number of samples used was 287 respondents, with the sampling technique using simple random sampling. The data source used is primary data, with the data collection method using a questionnaire. The data analysis technique used is multiple linear regression analysis. The results of hypothesis testing show that organizational support has a positive and significant effect on employee performance, and competence has a positive and significant effect on employee performance. The coefficient of determination is 0.511, meaning that organizational support and competence can explain variations in employee performance variables by 51.1 percent, so it still needs to be followed up with further research, especially related to employee performance.